Enhancing Patient Care Through Structured Assessment Of Supracondylar Fractures: A Quality Improvement Project At Holy Family Hospital, Rawalpindi Medical University - Waris, Hira; Akhtar, Rahman Rasool; Ahmed, Riaz; Haider, Muhammad; Javaid, Mohammad Mohsin; Ali, Waqas (Journal of Rawalpindi Medical College, 2024)
Objective: Aim of this QIP is to investigate the neurovascular status documentation of supracondylar fractures in pediatric population and to devise and implement a new assessment proforma for evaluation of these fractures. Methods: This QIP was conducted in two cycles at Department of Orthopedic Surgery, Holy Family Hospital from October 2022 to October 2023. The first cycle was retrospective data collection and second cycle was prospective data collection. In total, there were 112 children with supracondylar fractures. The evaluation was conducted in three stages: the initial stage consisted of examining the patient on presentation, the second stage focused on evaluating after applying plaster of Paris (POP)/backslab/manipulation, and the third stage involved assessing the patient post-surgery. Throughout each stage of evaluation, any changes in vascular assessment (Yes/No) and any changes in neurological assessment (Motor and Sensory) were documented. The data was analyzed using 95% confidence interval and a significance level set at p<0.05. Results: Cycle: 1 In cycle 1, pre-Operatively, 6 patients (11.5%) had documented neurological status, 25(48.07%) had documented vascular status, and 10 (19.2%) as "NVI." After POP/backslab/manipulation, neurological status was documented in 3 patients (5.8%), vascular status in 21(40.3%), and "NVI" in 8(15.4%). Postoperatively, neurological status in 5(9.6%), vascular status in 23(44.2%), and "NVI" in 16 patients (30.8%). Cycle: 2 On presentation in cycle 2, neurological status documentation was present in 41 patients (68.3%), vascular status documentation in 55(91.6%), and "NVI" in 40(66.7%). After POP/backslab/manipulation, neurological status documentation was in 48 patients (80%), vascular status documentation in 52(86.7%), and "NVI" in 53(88.3%). Postoperatively, neurological status documentation was in 52(86.7%), vascular status documentation in 56(93.3%), and "NVI" in 57(95.0%). Conclusion: This QIP suggest that structured assessment of supracondylar fractures can significantly enhance patient care.